If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -5 = 16 Reorder the terms: -5 + 3p = 16 Solving -5 + 3p = 16 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3p = 16 + 5 Combine like terms: -5 + 5 = 0 0 + 3p = 16 + 5 3p = 16 + 5 Combine like terms: 16 + 5 = 21 3p = 21 Divide each side by '3'. p = 7 Simplifying p = 7
| -6-4x=19 | | 0.30(15)+0.05x=(0.20)(x+15) | | 12-7x=26 | | 10x+19=3x+117 | | x-2+x+2=-4 | | 137-3x=42x+22 | | 7x+12=4x+102 | | 231-4x=41x+16 | | x+2x-15x=3x | | 19=4+3y | | -90x=30 | | x+3+x=-3 | | 7x+3=9x-2-2x | | 7(3x+6)=21x+42 | | |x|+|x+5|=7 | | 8a+3a-6a= | | -3500+60x=30 | | y=-(3/5)x-2 | | 2t^2-15t+7=0 | | 0.18(y-8)+0.12y=0.06y-0.3 | | 16a+19b+2c+3c-3b-3a= | | 18y^2/60y^5 | | 329*43*432*432=x | | 56-2x=34x+16 | | 1-6y=1+4y | | 5x^2+28x+15= | | y+y/3=12 | | 11m+6n-5m+8n= | | 24/1.5=x | | x-x-4=-2 | | -(2/5)^2 | | 2x-8(x+9)=2-(x-9) |